1991
DOI: 10.1111/j.1751-8369.1991.tb00399.x
|View full text |Cite
|
Sign up to set email alerts
|

Additions to the family Miroviaceae (Coniferae) from the Lower Cretaceous of West Greenland and Germany: Mirovia groenlandica n. sp., Tritaenia crassa (Seward) comb, nov., and Tritaenia linkii Magdefrau et Rudolph emend.

Abstract: The genus Tritaenia with its type species T. linkii Magdefrau et Rudolph emend, from the Wealden of Germany has been referred to the family Miroviaceae Bose et Manum, comprising Mesozoic and mostly Arctic conifer foliage with ‘Sciadopitys‐like’ stomatal distribution. Two other additions to the Miroviaceae, both from the Lower Cretaceous of West Greenland, arc Pityophyllum crassum Seward, now attributed to Tritaenia, and Mirovia groenlandica n. sp., described on leafy stems and detached leaves. Tritaenia has di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…A few sciadopityaceous fossil cones have been found in Mesozoic strata (e.g., Menzel, 1913;Bose, 1955Bose, , 1959, but none ofthem has been described anatomically. Among the structurally preserved fossil cones, those of Pseudovoltzia liebeana (Geinitz) Florin, from the Upper Permian of the Rhineland, described by Schweitzer (1963), are similar to the present cone in that they have lobed ovuliferous scales and inverted seeds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few sciadopityaceous fossil cones have been found in Mesozoic strata (e.g., Menzel, 1913;Bose, 1955Bose, , 1959, but none ofthem has been described anatomically. Among the structurally preserved fossil cones, those of Pseudovoltzia liebeana (Geinitz) Florin, from the Upper Permian of the Rhineland, described by Schweitzer (1963), are similar to the present cone in that they have lobed ovuliferous scales and inverted seeds.…”
Section: Discussionmentioning
confidence: 99%
“…Many fossil Sciadopitys-like leaves have been reported. However, Bose andManum (1990, 1991) concluded that most of the leaves from northern Europe and adjacent areas are not as similar to those of Sciadopitys as previously thought, and they assigned these leaves into the family Miroviaceae. Under these circumstances, the present specimen is particularly important because it provides evidence of a sciadopityaceous conifer in the Late Cretaceous ofJapan, as well as morphological and anatomical characteristics ofcones ofthe family Sciadopityaceae that supplement the characteristics exemplified by living S. verticillata.…”
mentioning
confidence: 90%
“…Parichiev (1968) joined Xenoxylon and the extant Taxodiaceae Sciadopitys (the umbrella‐pine, today endemic to Japan) on the basis of their palaeogeographic distribution and on the fact that Xenoxylon and Sciadopitys ‐like foliage are often found associated in Early Cretaceous sedimentary rocks all around the Arctic. It was demonstrated subsequently (Bose & Manum 1990, 1991) that this Sciadopitys ‐like foliage was not related to the modern genus Sciadopitys but to various different genera ( Mirovia , Oswaldheeria , Tritaenia , etc. ), which belong to the extinct family named Miroviaceae.…”
Section: Materials and Biogeographical Frameworkmentioning
confidence: 96%
“…Thus, the Majonicaceae from the Permian and Triassic could perhaps have contained a conifer that was the common ancestor of Sciadopitys as well as the taxodiaceous Cupressaceae. Several fossils resembling Sciadopitys from the Jurassic and Cretaceous are now attributed to the fossil family Miroviaceae (Bose and Manum, 1991;Manum, van Konijnenburg-van Cittert, and Wilde, 2000) but could well be closely related to this genus. Sciadopitys itself may also have been present from these periods (Manum, 1987) and was certainly present in the Late Cretaceous (Christophel, 1973;Saiki, 1992) and probably represents the last survivor of a split between its immediate ancestor and a lineage leading to the taxodiaceous Cupressaceae.…”
Section: Systematics-the Relationships Ofmentioning
confidence: 99%